PENGARUH CITRA MEREK (BRAND IMAGE), KUALITAS PRODUK, PERSEPSI HARGA, PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK HONDA DI MPM MOTOR - Irawan Dwiyanto; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to examine and analyze the influence of brand image, Product Quality, Price Perception, Sales Promotion on The Purchase Decision of Honda Products in Mpm Motor. Population and sample in this study were 78. The methods to collect the data was questionnaire. Data analysis in this study used SPSS version 14. In this study the application used to test the data were “validity test, reliability test, Normality test, multiple linear regression analysis, classical assumption test, and testing the research hypothesis”. The result in this study indicated that Brand image and Sales Promotion have a significant effect on Honda MPM Motor Purchase Decisions. Product Quality and Price perception have no significant effect on purchasing decisions. Keywords: Product Quality, Price Perception, Sales Promotion On The Purchase Decision